Maternal and perinatal outcomes in mixed antenatal care modality implementing telemedicine in the southwestern region of Colombia during the COVID-19 pandemic - María Fernanda Escobar; Juan Carlos Gallego; María Paula Echavarria; Paula Fernandez; Leandro Posada; Shirley Salazar; Isabella Gutierrez; Juliana Alarcon (BMC, 2023)
Abstract Introduction Contingency measures due to the COVID-19 pandemic limited access to routine prenatal care for pregnant women, increasing the risk of pregnancy complications due to poor prenatal follow-up, especially in those patients at high obstetric risk. This prompted the implementation and adaptation of telemedicine. Objective We aim to evaluate the maternal and perinatal outcomes of patients who received prenatal care in-person and by telemedicine. Methods We conducted a retrospective observational cohort study of pregnant women who received exclusive in-person and alternate (telemedicine and in-person) care from March to December 20,202, determining each group's maternal and neonatal outcomes. Results A total of 1078 patients were included, 156 in the mixed group and 922 in the in-person group. The patients in the mixed group had a higher number of prenatal controls (8 (6-9) vs 6 (4-8) p < 0.001), with an earlier gestational age at onset (7.1 (6-8.5) vs 9.3 (6.6-20.3), p < 0.001), however, they required a longer hospital stay (26 (16,67%) vs 86 (9,33%), p = 0.002) compared to those attended in-person; there were no significant differences in the development of obstetric emergencies, maternal death or neonatal complications. Discussion Incorporating telemedicine mixed with in-person care could be considered as an alternative for antenatal follow-up of pregnant women in low- and middle-income countries with barriers to timely and quality health care access.